Validation of Microarray for the Simultaneous Detection of Common α- and β-Thalassemia Gene Mutations - Sakorn Pornprasert (2019)
© American Society for Clinical Pathology 2019. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com. BACKGROUND: Methods for detecting the complex genetic characteristics of α- and β-thalassemias are required for preventing and controlling the outbreak of new cases. METHODS: We evaluated the accuracy and practical utility of microarray for simultaneous detection of α- and β-thalassemias. A total of 102 DNA specimens, which represented 25 different genotypes, were tested in parallel using the microarray and reference methods used in the thalassemia laboratory of the Associated Medical Sciences-Clinical Services Center (AMS-CSC), Chiang Mai, Thailand. RESULTS: A total of 100 (98.0%) DNA specimens were completely concordant between the microarray and reference methods, whereas discrepancies between the different methods were observed in only 2 DNA specimens with homozygous hemoglobin E (HbE). CONCLUSIONS: The microarray appeared to be a fast, easy to perform, and accurate method for simultaneous detection of α- and β-thalassemias in Thailand and Southeast Asian countries. However, this technique needs to be improved and validated in a larger number of specimens with homozygous HbE before further routine laboratory use.